Urban Structures and Human Psychology: A geocritical study of J.G Ballard’s Highrise and Cocaine Nights - Ahmed, Syeda Nubaira (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2020.